Bispecific antibodies in immunotherapy for acute leukemia: latest updates from the 66th annual meeting of the American society of hematology, 2024 - Cao, Weijie; Ma, Shuhan; Han, Lijie; Xing, Hanzhou; Li, Yingmei; Jiang, Zhongxing; Guo, Xuejun; Yu, Jifeng (Frontiers in Oncology, 2025)
Bispecific antibodies (BsAbs) are cutting-edge immunotherapy agents that can bind two distinct antigens or epitopes simultaneously. They hold significant potential in targeting leukemic cell markers and activating immune cells like T cells or NK cells to eliminate malignant cells. BsAb treatments showed encouraging outcomes for both acute myeloid leukemia (AML) and acute lymphoblastic leukemia (ALL). In relapsed/refractory (R/R) ALL, BsAbs improved overall survival (OS) and achieved measurable residual disease (MRD) negativity in most patients. Blinatumomab plus standard chemotherapy or in combination with other treatments, such as Mini-Hyper-CVD and Inotuzumab Ozogamicin, improved disease-free survival (DFS) in B-ALL. In AML and related conditions, novel BsAbs like AFM28 (CD123xCD16A) and Vibecotamab (CD123xCD3) showed promising efficacy in heavily pretreated R/R AML and in MDS/CMML following the failure of treatment with hypomethylating agents (HMA). The meeting underscored the transformative potential of BsAbs, especially in ALL-focused trials, with ongoing research aiming to evaluate their safety and efficacy in broader patient populations and combination regimens. This summary highlights the latest progress in BsAb-based immunotherapy presented at the ASH 2024 meeting, held from December 7–10 in San Diego, California.